Internal market orientation in law firms– evaluation of internal marketing techniques used for talent retention, job satisfaction and competitive advantage. - Patt, Tanja / TMP (2009)
This management project intends to assess the level and the outcome of internal market orientation in law firms and the various internal marketing techniques used by law firms in order to maintain a satisfied workforce and fight the obstacles of employee retention. For the purpose of this project, eight law firms of roughly the same size and operating in the same area have been interviewed about their internal market orientation and their views on employee motivation. In the course of the project, it will be examined in how far the marketing and human resource departments within these law firms are actually working together compared to the dimension in which they should or could work together in order to produce synergy effects for a successful workplace design. Especially the definition of adequate financial and non-financial incentives to motivate employees and successful designs of such incentive schemes which may be used to motivate employees to stay with the firm and to go the extra mile in delivering added value to clients will be under scrutiny. It will further be examined in how far both the firms and their employees benefit from entering into long-term high-value employment relationships with each other and whether the establishment of an internal market orientation may lead to a sustainable competitive advantage for the law firms.